Differentiation of Steroidogenic Cells in the Developing Adrenal Gland of Testudo hermanni Gmelin, 1789 (Chelonian Reptiles). (30th October 2012) - Chimenti, C.; Accordi, F.
Summary: The aim of this study was to investigate the development and differentiation of steroidogenic cells in the embryonic adrenal gland of Testudo hermanni using histological, histochemical, immunohistochemical and ultrastructural methods. The 26 developmental stages were divided into three periods: early (stages 1–18, up to 20 days of incubation), intermediate (stages 19–22, incubation days 21–35) and advanced (stages 23–26, from incubation day 36 to hatching). A small presumptive bud of steroidogenic cells was visible at the end of the early period, protruding into the coelom from the lateral wall of intermediate mesoderm. Ultrastructural characteristics suggested that young and scarcely differentiated cells could already be able to perform steroidogenic activity: lipid droplets, large amount of SER and RER, small rounded mitochondria with variously shaped cristae and dense matrix. The cell membrane showed microvilli and coated pits. During the intermediate period, the interrenal bud deepened into the haemopoietic tissue, close to the mesonephros and the newly formed metanephros. The ultrastructural, immunohistochemical and immunocytochemical characteristics pointed to enhanced steroidogenic activity. The contact with both kidney types (mesonephros and metanephros) continued in the advanced period, and chromaffin cells were also extensively mixed with steroidogenic cells. This is a peculiar feature of chelonian adrenal gland, in comparison with that of other reptiles. The variable cytological characteristics of embryonic steroidogenic cells in the advanced period suggest a four‐phase cycle of steroidogenic activity.